Survival, Neurocognitive, and Functional Outcomes After Completion of Staged Surgical Palliation in a Cohort of Patients With Hypoplastic Left Heart Syndrome - Joseph Atallah; Gonzalo Garcia Guerra; Ari R. Joffe; Gwen Y. Bond; Sunjidatul Islam; M. Florencia Ricci; Mohammed AlAklabi; Ivan M. Rebeyka; Charlene M. T. Robertson (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Management of patients with hypoplastic left heart syndrome has benefited from advancements in medical and surgical care. Outcomes have improved, although survival and long‐term functional and cognitive deficits remain a concern. Methods and Results This is a cohort study of all consecutive patients with hypoplastic left heart syndrome undergoing surgical palliation at a single center. We aimed to examine demographic and perioperative factors from each surgical stage for their association with survival and neurocognitive outcomes. A total of 117 consecutive patients from 1996 to 2010 underwent surgical palliation. Seventy patients (60%) survived to the Fontan stage and 68 patients (58%) survived to undergo neurocognitive assessment at a mean (SD) age of 56.6 months (6.4 months). Full‐scale, performance, and verbal intelligence quotient, as well as visual‐motor integration mean (SD) scores were 86.7 (16.1), 86.3 (15.8), 88.8 (17.2), and 83.2 (14.8), respectively. On multivariable analysis, older age at Fontan, sepsis peri‐Norwood, lowest arterial partial pressure of oxygen postbidirectional cavopulmonary anastomosis, and presence of neuromotor disability pre‐Fontan were strongly associated with lower scores for all intelligence quotient domains. Older age at Fontan and sepsis peri‐Norwood remained associated with lower scores for all intelligence quotient domains in a subgroup analysis excluding patients with disability pre‐Fontan or with chromosomal abnormalities. Conclusions Older age at Fontan and sepsis are among independent predictors of poor neurocognitive outcomes for patients with hypoplastic left heart syndrome. Further studies are required to identify the appropriate age range for Fontan completion, balancing a lower risk of acute and long‐term hemodynamic complications while optimizing long‐term neurocognitive outcomes.